THE DISTINCTIVE APPROACH OF SHAYKH MUHAMMAD SADIQ TO THE ISSUES OF RADICALIZATION AND MISUNDERSTANDING OF ISLAMIC TEACHINGS (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the processes of radicalization and the problems of misinterpreting Islamic teachings in a contemporary context. In particular, the distinctive approach of Shaykh Muhammad Sadiq Muhammad Yusuf is placed at the center of attention. In his works, the principles of explaining religious texts in a moderate, consistent, and life-connected manner are advanced, and this approach is viewed as an important factor in preventing radical views. The article examines questions of forming sound religious thinking in the minds of young people on the basis of Shaykh Muhammad Sadiq Muhammad Yusuf’s views on religious exegesis and jurisprudence. Furthermore, it is established that an evidential, balanced, and logical approach against extremist interpretations is predominant in his method. The conclusion advanced is that this approach can serve as an effective methodological foundation in the contemporary religious-enlightenment process.
Keywords: radicalization; religious extremism; interpretation of Islam; Shaykh Muhammad Sadiq Muhammad Yusuf; religious thinking; moderate Islam